Bloody Diarrhoea anl0ng Children under five years of Age in Tikirit Teaching Hospital - Jasim, Thamer Mutlek (AL-Kindy College Medical Journal, 2009)
ObjectiveIs to study the causes of bloody diarrhea in in (50)cases (37%) , Shigella spp in (25) cases (18% andchildren under five years of age and to clarify their relations Campylobacter jejuni Icases only (0.75%)to the type offood and mothers educational level ConciusionBloody diarrehea is common in children undermethods Ahospital based study was carried out at tikreet 5years age who were admitted to Tikreet Teaching Hospitalteaching Hospital in Tikreet city on 133 children who were in Tikreet city , There is astrong positive relationshipadmitted to the hospital with bloody diarrehea their ages between the occurrence of bloody diarrehea and the type ofrange between one month -5years. The period study is from food. Education of the mother plays an important rule for(January200 I-July 2001). the occurrence of bloody diarrehoea, mostly those whoResults The pathogens causing bloody diarrhea were were illitrate